Pengaruh DPK, FDR, NPF, dan SBIS Terhadap Pembiayaan UMKM pada BUS di Indonesia - Anisa Galih Wulandari; Iwan Setiawan; Ade Ali Nurdin (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to determine the effect of TPF, NPF, FDR and BICS on MSME financing in the observation period, namely January 2014-September 2021.The analytical method used in this study is used in this study is multiple linear regression analysis using the eviews 12 program. The results show that TPF, NPF, FDR and SBIS simultaneously have a significant effect on MSME financing at Islamic Commercial Banks in Indonesia for the period January 2014 - September 2021. And the DPK variable, FDR, NPF and SBIS have a positive partial influence on the financing of Micro, Small and Medium Enterprises at Islamic Commercial Banks in Indonesia for the period January 2014 - September 2021.